2013
DOI: 10.3382/ps.2012-02486
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and amino acid profiles of goose muscles from native Polish breeds

Abstract: The aim of the study was to compare the chemical and amino acid composition of breast (pectoralis major) and thigh (biceps femoris) muscles in 17-wk-old geese from 2 Polish conservative flocks: Rypińska (Ry, n = 20) and Garbonosa (Ga, n = 20). The geese were fed ad libitum during the experimental period on the same complete feed. Genotypes affected the moisture and fat content of breast and thigh meat. The Ga geese were characterized by higher moisture as well as lower fat lipid content compared with the Ry br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 10 publications
4
22
1
1
Order By: Relevance
“…Statistical analyses showed significant differences (p ≤ 0.05) between breeds and between sexes within breeds for the studied trait. The obtained results demonstrate the high impact of breed and sex on body weight in the studied geese breeds, which is consistent with studies conducted elsewhere [22,23]. Based on the analysis of genotypes and the occurrence of significant statistical relationship for the characteristics of BW, the identified polymorphism cannot be clearly linked to the body weight of the studied geese breeds.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Statistical analyses showed significant differences (p ≤ 0.05) between breeds and between sexes within breeds for the studied trait. The obtained results demonstrate the high impact of breed and sex on body weight in the studied geese breeds, which is consistent with studies conducted elsewhere [22,23]. Based on the analysis of genotypes and the occurrence of significant statistical relationship for the characteristics of BW, the identified polymorphism cannot be clearly linked to the body weight of the studied geese breeds.…”
Section: Discussionsupporting
confidence: 88%
“…Recent studies proved the high value of lipids and amino acids composition of local geese breeds [21]. It is well accepted that the body weight, as well as qualitative traits in geese, are strongly dependent on genotype [22][23][24]. However, the molecular background of meat production remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…This trend is very similar to the results of our study and is because the lipid content of the breast increases with age at the expense of the water content. Okruszek et al [ 5 ] observed significantly different fat content between two native polish goose breeds. When compared the meat fat content of the White Koluda hybrid strains [ 11 ] to the fat content of the traditional goose breeds [ 5 ], lower values were detected in traditional breeds of geese.…”
Section: Discussionmentioning
confidence: 99%
“…Over time special hybrids have been bred for intensive meat production system. However, in recent years, attention has focused again on the meat production of native breeds of geese [ 3 , 4 , 1 , 5 ]. These breeds of geese are characterized by good musculature and low carcass fatness, as well as high dressing percentage [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…, 2012b; Biesiada-Drzazga i in. 2011], w składzie aminokwasowym białka [Okruszek 2013] oraz we właściwościach fizykochemicznych mięśni [Ács i in. 1995;Butler i in.…”
Section: Wpływ Genotypu Na Skład Tkankowy Tuszki Oraz Skład Chemicznyunclassified